KELOMPOK TANI DALAM MEMBANGUN KAMPUNG ANGGUR DI KELURAHAN AIR PUTIH KECAMATAN TUAH MADANI KOTA PEKANBARU - ", Ampurilus; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research aims to find out how farming groups build wine villages. The method used is to use descriptive qualitative methods. As for the formulation of the problem in this study (1) How is the participation of farmers groups in building wine village tours in The White Water Village? (2) What are the factors that affect the participation of farming groups in building wine village tours in The White Water Village? Data collection techniques in this study in the form of questionnaires, observations, documentation. This research was conducted at White Water Village, Tuah Madani Subdistrict, Pekanbaru City with a total of 16 subjects. The data analysis technique in this study is quantitatively descriptive using SPSS version 23. The results of the study explained that the participation of peasant groups is a form of mind participation with indicators of 5 statements classified as high, the form of energy participation with 4 statements is classified as high, the participation of goods with 4 statements is classified as high and the participation of money with 4 statements is classified as high after factors that affect the participation of the peasant group, namely education, employment, income, and knowledge.  Keywords: Participation, Factors, Peasant Groups